Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content 1. Family reform and its link to solving the problems facing working women and their multiple roles: Applied study on a sample of women working in the private sector in Jeddah Mr. Samir Khalaf Atiq Al-Mutairi 2. Symbol Aesthetics in Mesopotamia Pottery Mr. Omar Mohmmad Samer Abdui-Hafedh, Prof. Hamideh Jafari 3. The Effectiveness of a Proposed Educational Unit for Training on the Wilcom Program in Machine Embroidery Technology Course Mrs. Amani Abdu Ahmad Alzayla’aee, Co-Prof. Kherah Award Alzahrani 4. Palestinian Scientific Research from the Perspective of Bachelor’s Students: Exploring Reality and Aspirations Dr. Osama Issam Matar , Dr. Reem Mashhour Jawabreh , Mrs. Haya Yaser Radwan, Dr. Mohammad Shareef Ayyash, Mr. Thaher Mohamed Gharabeh, Mr. Abedelrahman Aqel Alhajhamad1, Dr. Ashraf Mohammed Abualrob, Mrs. Aseel Adly Halabi, Mr. Diya Mohammed Abu Shomer, Mrs. Sherin Wael Kaleef 5. Negative manifestations on occasion of joys and their impact on Saudi society: A study applied to Afif governorate Mr. Talal Fahd Munir Al-Otaibi 6. Personal Data Protection in the Kingdom of Saudi Arabia, EU and UK GDPR: A Comparative Study Mr. Najim Abdullah Al-Shammari 7. Evaluation of service area and ease of access to public hospitals in Riyadh using GIS Mr. Sahoud Rahim Al-Adhyani 8. The Role of Social Work in Facing the Negative Effects of Cyberbullying on Adolescents in Saudi Arabia Mrs. Meaad Shahad Zayed Al-Sulami